Comparison of the effect of desloratadine and montelukast combined treatment with desloratadine monotherapy on clinical symptoms and quality of life of patients with persistent allergic rhinitis - Meghdad Rahati; Amir hossein Ahsaniarani; Shayan Ramezanpour; Saeed Amini (مجله علوم پزشکی فیض (پیوسته))
Background and Aim: Allergic rhinitis is the most common atopic disorder and a chronic inflammatory disease of the airways, which can lead to disruption and decrease the patient's quality of life in the long term. This study was conducted to compare the effects of desloratadine and montelukast combined treatment with desloratadine monotherapy on clinical symptoms and quality of life of patients with persistent allergic rhinitis. Methods: This double-blind controlled clinical trial was conducted in the Ear, Nose and Throat Clinic of Metini Medical Training Center affiliated to Kashan University of Medical Sciences, on 56 patients with persistent allergic rhinitis. Patients were randomly assigned into two groups to receive combined treatment of montelukast (10 mg) and desloratadine (5 mg daily) or single drug treatment of desloratadine for a period of 6 weeks. At the beginning and end of the study, the quality of life and severity of clinical symptoms were evaluated by completing the miniRQLQ questionnaire and nasal symptom score in both groups. Results: In the intervention group (combined treatment of montelukast and desloratadine) and the control group (single drug treatment of desloratadine), the quality of life increased significantly after receiving the treatment compared to before (P<0.05), although in the intervention group, this increase was more than that in the control group. Moreover, the intensity of clinical symptoms decreased significantly after receiving the treatment compared to before (P<0.01), although this reduction was more in the intervention group. Conclusion: It can be concluded that in patients with stable allergic rhinitis, the combined treatment of montelukast and desloratadine and the single drug treatment of desloratadine are effective in improving the quality of life and reducing the severity of clinical symptoms.